Determining biochemical qualitative indicators of grapes during long-term storage - Nabiyev, Ahad; Kazimova, İlhama; Mammadaliyeva, Maryam; Maharramova, Sevinj; Nasrullayeva, Gunash; Yusifova, Mehriban (Eastern-European Journal of Enterprise Technologies, 2024)
This paper reports a study aimed at determining the biochemical quality indicators of grapes during long-term storage. The object of research was nine table varieties of ripened grapes. These include white varieties – Tabrizi, Karaburnu, White Shasla, Agadai; pink varieties – Nimrang, Marandi Shamakhi, Taifi pink; red varieties – Kyzyl raisins and Hamburg Muscat. The grapes were stored in refrigerators for 5–6 months, at a temperature of 0–1 °C and air humidity of 87–95 %. The grapes were studied before planting and 30–40 days before the end of storage. Long-term refrigerated storage of grapes using weekly fumigation with sulfur dioxide is accompanied by a decrease in the activity of oxyreductases and a gradual increase in the activity of pectinesterase. This causes changes in the quantity and proportions of nutrients and other chemical components that determine the nutritional and biological value of the final product. It was revealed that during the sale of ripened grapes stored using weekly fumigation with sulfur dioxide, the activity of the studied oxyreductases is slightly restored in pink varieties – Nimrang, Taifi pink, and in white varieties – in Karaburnu and Tabrizi. In the Marandi Shamakhi variety, the activity of enzymes does not change, therefore, for a long time in these grape varieties, especially in the Marandi Shamakhi variety, darkening and softening of the berries are not observed during their sale. Among the studied table grape varieties, Tabrizi, Karaburnu, Nimrang, and Marandi Shamakhi, with long-term refrigerated storage using weekly fumigation with sulfur dioxide, have the longest shelf life; under a controlled gas environment, the results reported here could prove useful in practice